Analisis Dampak Beban Kerja dan Gaji terhadap Kinerja Karyawan Tenaga Sukarela Rumah Sakit: Perspektif Potensi Kecurangan yang Terjadi - Ahmad Hijri Alfian; MA Irfan Rahmana (Jurnal Ekonomi dan Bisnis, 2023)
As an effort to realize the vision and mission of the Hospital, employee performance must increase. In the process of improving employee performance, it must pay attention to factors that can improve performance. However, this work should not be done haphazardly and must still be in accordance with the Hospital SOP. This study aims to determine the effect of workload and salary on the performance of volunteer employees, as well as to see the potential for fraud that may occur during the process of completing work.The population in this study were all temporary staff including nurses and nutritionists who worked at one of the hospitals in Semarang, with a total sample of 76 respondents. The data source used is primary data using a questionnaire. The data analysis technique used is multiple linear regression.The results showed that the workload variable has a negative effect on employee performance. Furthermore, salary has a positive effect on employee performance. Additional questionnaires show that high workloads and salaries that are not in line with expectations but performance demands remain high, will have the potential to cause activities that are not in accordance with the provisions and SOPs of the Hospital